(untitled) (Indian Journal of Child Health, 2021)
Background: Beta-thalassemia is considered to be the most frequent hereditary blood disorder worldwide. Lipid abnormalities have been detected in different types of beta-thalassemia thus pre-disposing them to pre-mature atherosclerosis. Objectives: To study the lipid profile in beta-thalassemia major (?-TM) children and establish its co-relation with various parameters. Materials and Methods: A total of 100 diagnosed patients of ?-TM age 1–18 years and 100 subjects in the control group matched for age and sex were enrolled. For detecting a minimum difference of at least 20 mg/dl of triglyceride between the two groups, the required sample size was 81 subjects in each group, which was further, enhanced and rounded off to 100 subjects in each group. Univariate and multivariate regression analysis was done to establish a correlation of lipid profile with various parameters. Results: Total cholesterol (TC) was lower in thalassemia patients as compared to controls 104.45 versus 117.97 (p<0.001). Triglycerides (TG) values were higher in thalassemia patients as compared to controls 155.96 versus 73.95 (p<0.001). Low high-density lipoprotein (HDL) cholesterol was observed in thalassemia patients as compared to controls 36.33 versus 43.85 (p<0.001). No statistically significant difference was observed between low-density lipoprotein (LDL) values between patients and controls 55.89 versus 54.53 (p<0.817). The pro-atherogenic TC: HDL ratio was significantly higher (3.21±0.88 vs. 2.91±1.06) in patients as compared to controls (p<0.001). By multivariate regression analysis, we observed that there was a significant decrease in TC with advancing age (p=0.002, ?=–0.283) and with a decrease in hemoglobin (p=0.028, ?=0.425) but TC was not related to hematocrit, gender, liver enzymes, serum bilirubin, chelating agents and serum ferritin. LDL cholesterol also had significant negative correlation with age (p = 0.015, ? = ?0.240) and positive correlation with hemoglobin (p=0.033, ?=0.211). HDL cholesterol and TG were not related to age, gender, hemoglobin, hematocrit, liver enzymes, chelating agents, and serum ferritin. Conclusion: ?-TM patients have hypertriglyceridemia and hypocholesterolemia. Thus, early detection of these abnormalities will help to prevent cardiovascular complications.